2023
DOI: 10.3390/medicina59040800
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Critical Flicker Fusion Frequency: Which Confounders? A Narrative Review

Abstract: The critical flicker fusion frequency (cFFF) refers to the frequency at which a regularly recurring change of light stimuli is perceived as steady. The cFFF threshold is often assessed in clinics to evaluate the temporal characteristics of the visual system, making it a common test for eye diseases. Additionally, it serves as a helpful diagnostic tool for various neurological and internal diseases. In the field of diving/hyperbaric medicine, cFFF has been utilized to determine alertness and cognitive functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 89 publications
2
6
0
Order By: Relevance
“…We agree with Muth et al [ 1 ] that the state of knowledge about CFFF still has many gaps and ambiguities. Possibly, an international cooperation involving key research teams exploring the intricacies of flickering light could represent an important step toward developing general protocol standards.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…We agree with Muth et al [ 1 ] that the state of knowledge about CFFF still has many gaps and ambiguities. Possibly, an international cooperation involving key research teams exploring the intricacies of flickering light could represent an important step toward developing general protocol standards.…”
supporting
confidence: 92%
“…We first want to thank the authors of the excellent review for their contributions to summarizing the confounders associated with critical flicker fusion frequency (CFFF) [ 1 ]. We read this review with great interest as the publication significantly broadened with this aspect of the summary we wrote [ 2 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As variation between individuals of the same species is present in many aspects of visual perception, we aimed to evaluate whether this is also the case for critical flicker fusion thresholds, using healthy human participants. CFF has been well studied in humans, and previous research has found that critical flicker fusion thresholds are affected by many physiological factors [ 10 ]. For instance, different parts of our retina have different levels of sensitivity to flicker [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…First and foremost, we like to express our gratitude for the praise bestowed upon our narrative review [1], particularly as it comes from a group of such esteemed reputation [2].…”
mentioning
confidence: 99%